A comparative analysis of structural properties on single and poly-crystalline potassium sulfate crystals at shock wave loaded conditions. (December 2021) - Sivakumar, A.; Sahaya Jude Dhas, S.; Almansour, Abdulrahman I.; Kumar, Raju Suresh; Arumugam, Natarajan; Perumal, Karthikeyan; Martin Britto Dhas, S.A.
Abstract: In recent years, the investigation of the effect of shock waves on crystalline materials has emerged as a prolific research area in materials science branch. The impact of shock waves on K2 SO4 was investigated such that the molecular and structural stabilities under pre and post-shock wave loaded conditions at Mach number 2.2 with 50 and 100 shocks were established. Molecular stability of the test samples has been identified making use of FTIR spectrometer and the structural stability of the samples has been investigated by a Powder X-ray diffractometer (PXRD) which reveals that shock waves induce lattice orientational changes and micro distortions but, the original crystal system is not affected. The above-mentioned crystallographic studies show the impressive physical properties of K2 SO4 which also has a stable crystal structure under shock wave loaded conditions. A comparison of single and poly-crystalline structural responses has been made with respect to the number of shock pulses. The fascinating findings of the shock wave impacts on K2 SO4 samples are clearly discussed in this article. Highlights: Crystallographic phase stability of the poly-crystalline and single crystalline K2 SO4 at shocked conditions is reported. FT-IR and XRD results show the stable crystal structure of poly-crystalline samples at shocked conditions. Poly-crystalline K2 SO4 sample has relatively high structural stability and shock resistance compared to the single crystal.